SELF-ACUPRESSURE TO LOWER BLOOD PRESSURE ON OLDER ADULTS WITH HYPERTENSION - Agus Citra Dermawan; Santun Setiawati; Raden Siti Maryam (Poltekkes Kemenkes Semarang, 2019)
Hypertension is often suffered by older adults, which directly can impact their health and quality of life. One of the non-pharmacological management for patients with hypertension is through acupressure to accelerate blood-flow circulation and to reduce blood pressure. This study aims to determine the self-acupressure effect on the elderly with hypertension in Cilincing Health Center in North Jakarta. This research used a quasi-experimental involving control and intervention group. Thirty-six elderlies were involved in this study divided into two groups. Findings showed that there were significant differences in the intervention group between the results of systolic and diastolic measurements before and after acupressure (p-value=0,000). The findings suggest that families can apply self-acupressure as a support system for older adults with hypertension.